Kurikulum Merdeka dan Merdeka Belajar: Kajian Teologis, Efektivitas dan Tantangan Guru Pendidikan Agama Kristen dan Budi Pekerti - Mendrofa, Arianto (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2024)
This research was carried out with the aim of analyzing theological studies regarding the challenges of PAK and Budi Pekerti teachers in the effectiveness of implementing the independent learning curriculum.  So the method used in this research is a descriptive quantitative approach to effectiveness. The research subjects were Christian students registered at Surakarta City Public Middle Schools, totaling 872 students. The results of data analysis showed that 29.9% stated that moral cultivation would be effective if taught by spiritual mentors in the Church. Meanwhile, 67.4% stated that teachers at school were very effective when instilling morals in their students. In implementing the Merdeka Curriculum, there are challenges for Religious Education and Character Teachers, namely the implementation of general education and the cultivation of character based on the six key dimensions of the Pancasila Student Profile competencies. AbstrakPenelitian ini dilaksanakan dengan tujuan untuk menganalisis survei efektivitas pelaksanaan kurikulum merdeka dan merdeka belajar dalam perspektif kajian teologi terhadap tantangan guru Pendidikan Agama Kristen dan Budi Pekerti.  Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif deskriptif. Subyek penelitian adalah siswa Kristen yang terdaftar di SMP Negeri se-Kota Surakarta yang berjumlah 872 siswa. Hasil analisa data menunjukkan 29,9% menyatakan bahwa penanaman moral akan efektif jika diajarkan oleh pembina rohani di Gereja. Sedangkan 67,4% menyatakan guru di sekolah sangat efektif apabila menanamkan moral kepada peserta didiknya. Dalam pelaksanaan Kurikulum Merdeka dan Merdeka Belajar terdapat tantangan bagi Guru PAK dan Budi Pekerti yakni terjadinya general education dan penanaman budi pekerti mengacu pada keenam kompetensi dimensi kunci Profil Pelajar Pancasila.